GRAMMATICAL ERROS COMMITED BY JUNIOR HIGH SCHOOL STUDENTS IN SPEAKING ENGLISH - Anggana, IPS (Universitas Pendidikan Ganesha, 2018)
The purposes of this study are to analyze the types of grammatical errors and to know the types of grammatical error which are frequently made by the junior high school students in speaking English. The research design in this study was descriptive qualitative design with the eighth grade students in second semester of SMP Negeri 4 Singaraja as the population and 33 students were chosen to be the sample. The instruments that were used to collect the data were researcher and video recorder. The result showed that students made error in omission, addition, misinformation, and misordering. The total of errors reaches 61 times. The highest frequency of error is omission which is 62.30%. The second frequency of error is misordering, 18,4%. The third frequency of error is addition which is 14,75%. The last frequency of error is misformation that is 4,91%. Grammatical error, Speaking